Dissecting the Genetic Architecture of Melon Chilling Tolerance at the Seedling Stage by Association Mapping and Identification of the Elite Alleles - Hou, Juan; Zhou, Ya-Feng; Gao, Lu-Yin; Wang, Yan-Ling; Yang, Lu-Ming; Zhu, Hua-Yu; Wang, Ji-Ming; Zhao, Sheng-Jie; Ma, Chang-Sheng; Sun, Shou-Ru; Hu, Jian-Bin (Frontiers in Plant Science, 2018)
Low temperature is an important abiotic stress that negatively affects morphological growth and fruit development in melon (Cucumis melo L.). Chilling stress at the seedling stage causes seedling injury and poor stand establishment, prolonging vegetative growth and delaying fruit harvest. In this study, association mapping was performed for chilling tolerance at the seedling stage on an expanded melon core collection containing 212 diverse accessions by 272 SSRs and 27 CAPSs. Chilling tolerance of the melon seedlings was measured by the chilling injury index (CII) in 2016 and 2017. Genetic diversity analysis of the whole accession panel presented two main groups, which corresponded to the two subspecies of C. melo, melo and agrestis. Both the subspecies were sensitive to chilling but with agrestis being more tolerant. Genome-wide association study (GWAS) was conducted respectively on the whole panel and the two subspecies, totally detecting 51 loci that contributed to 74 marker-trait associations. Of these associations, 35 were detected in the whole panel, 21 in melo, and 18 in agrestis. About half of the associations identified in the two subspecies were also observed in the whole panel, and 7 associations were shared by both subspecies. CMCT505_Chr.1 was repeatedly detected in different populations with high phenotypic contribution and could be a key locus controlling chilling tolerance in C. melo. Nine loci were selected for evaluation of the phenotypic effects related to their alleles, which identified 11 elite alleles contributing to the seedling chilling tolerance. Four such alleles existed in both the subspecies and 6 in either of the two subspecies. Analysis of 20 parental combinations for their allelic status and phenotypic values showed that the elite alleles collectively contributed to enhancement of the chilling tolerance. Tagging the loci responsible for chilling tolerance may simultaneously favour dissecting the complex adaptability traits and elevate the efficiency to improve chilling tolerance using marker-assisted selection in melon.